Evaluation of land suitability for soybean production using GIS-based multi-criteria approach in Kudan Local Government area of Kaduna State Nigeria - Fatihu Kabir Sadiq; Suleiman Lawan Ya'u; Jamila Aliyu; Lemuel Musa Maniyunda (Environmental and Sustainability Indicators, 2023)
The demand for food production in achieving Sustainable Development Goals, such as poverty eradication and food security and nutrition in developing countries like Nigeria has led to intensive agriculture, resulting in decreased soil quality and environmental challenges. To address these issues, land suitability evaluation plays a crucial role in designing sustainable land use and management systems. This evaluation provides valuable insights for farmers and policymakers to optimize soybean production, enhance crop yield, and promote sustainable agricultural development. The research covers 39,057 ha (ha) and it considers multiple criteria such as soil properties, slope, Normalized Difference Vegetation Index (NDVI), and land use/land cover (LULC) of the study area. Soil data and land use/land cover information were obtained and processed using geostatistical techniques and interpolation methods in ArcGIS. An Analytical Hierarchy Process (AHP) was employed to determine the overall importance of the evaluation criteria. This study revealed that 14.14% of the area falls into the moderately suitable class, a significant proportion (83.77%) of the area is marginally suitable for growing soybean, and the remaining proportion (2.09%) is deemed unsuitable. Drainage condition was identified as one of the major limiting factors for soybean cultivation in the region. Management practices such as drainage construction, organic residue incorporation, and appropriate fertilizer application were suggested to improve land suitability. The outcome of this study has shown that integrating RS and GIS techniques in land suitability assessment facilitates evidence-based decision-making and supports effective land use planning for increased agricultural productivity and environmental sustainability.